Gene Expression Pattern and Regulatory Network of α-Toxin Treatment in Bombyx mori. (5th March 2019) - Feng, Tieshan; Lin, Ping; Gong, Jiao; Cheng, Dong; Yang, Xi; Zhang, Quan; Cheng, Tingcai
Abstract : Bacillus bombyseptieus is a pathogen of Bombyx mori ; it can cause bacterial septicemia in silkworm. One of the components of the parasporal crystal toxin of B. bombyseptieus, α -toxin, plays an important role in the process of infection in silkworm. In this study, we investigated the immune response of silkworm induced by α -toxin by using RNA-seq. We compared the changes in gene expression in the midgut, fatbody, and hemocytes of silkworm and in the B. mori embryonic cell line (BmE) after treatment with α -toxin and identified 952 differentially expressed genes and 353 differentially expressed long noncoding RNAs (lncRNAs). These regulated genes in different tissues were found to be enriched in different pathways. The upregulated genes in the midgut were mainly involved in peptidoglycan catabolic process and tyrosine kinase signaling pathway, whereas the downregulated genes were mainly involved in chitin metabolic pathways. The upregulated genes in fatbody were also involved in peptidoglycan catabolic process, but they were for a different peptidoglycan subtype. Further, genes encoding cecropins were enriched in the fatbody. The downregulated genes were mainly involved in the metabolic pathways of fundamental substances such as cellular protein metabolic process and nucleobase-containing compound metabolic process. These results suggest that α -toxin can induce various immune responses in silkworm, and further studies are warranted to understand the mechanism of α -toxin action in silkworm. Further, lncRNAs and differentially expressed genes were correlated using coexpression network analysis. Our findings revealed potential candidate genes and lncRNAs that might play important physiological functions in the immune response to α -toxins in silkworm.